2011
DOI: 10.3390/ijerph8073019
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ethanol Consumption on Insulin Resistance Are Only Applicable to Subjects Without Obesity or Insulin Resistance; Drinking is not Necessarily a Remedy for Metabolic Syndrome

Abstract: Although moderate drinking has been shown to lower insulin resistance levels, it is still unclear whether alcoholic beverages could be remedies for insulin resistance. To elucidate this, the correlation between levels of ethanol consumption and insulin resistance were cross-sectionally examined in 371 non-diabetic male Japanese workers. Multiple regression analysis demonstrated that the ethanol consumption level was inversely correlated with the insulin resistance level assessed by homeostatic model assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…It was also reported that alcohol reduces insulin production of β-cell and aggravates endoplasmic reticulum stress by inhibiting muscarinic signaling and protein kinase C, which results in insulin secretion dysfunction [34]. Consistent with the previous findings [31,32], our results showed that the more AUDIT score increased, the more HOMA-B score decreased, indicating that excessive alcohol intake is related to dysfunction of insulin secretion. Our results are distinct from the earlier reports in that AUDIT score was used in order to comprehensively evaluate the alcohol-related problem behavior in addition to the amount and frequency of alcohol intake.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also reported that alcohol reduces insulin production of β-cell and aggravates endoplasmic reticulum stress by inhibiting muscarinic signaling and protein kinase C, which results in insulin secretion dysfunction [34]. Consistent with the previous findings [31,32], our results showed that the more AUDIT score increased, the more HOMA-B score decreased, indicating that excessive alcohol intake is related to dysfunction of insulin secretion. Our results are distinct from the earlier reports in that AUDIT score was used in order to comprehensively evaluate the alcohol-related problem behavior in addition to the amount and frequency of alcohol intake.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported that alcohol consumption influences β-cell function [21,30,31,32]. High amounts of alcohol consumption are associated with a decrease in HOMA-B score function in both males [30] and females [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[83]. An inverse relation between moderate alcohol consumption and insulin resistance has been reported in normalweight subjects, but not in overweight/obese patients with a Homeostasis Model of Assessment (HOMA) index <2 [84].…”
Section: Alcohol and Insulin Sensitivitymentioning
confidence: 99%
“…Although null findings have been reported [13], evidence has also suggested that, in combination with sex, adiposity moderates the relation of alcohol consumption to metabolic factors. For example, adiposity, as measured by BMI, moderated the relation of alcohol consumption to IR and fasting insulin with moderate alcohol consumption associated with lower IR and fasting insulin in men with normal BMIs (<25 kg/m 2 ), but not those with BMIs greater than or equal to 25 kg/m [14]. In women, however, a different pattern has been observed.…”
Section: Introductionmentioning
confidence: 99%